Sampling properties of estimators of nucleotide diversity at discovered SNP sites - Renwick, Alexander; Bonnen, Penelope E.; Trikka, Dimitra; Nelson, David L.; Chakraborty, Ranajit; Kimmel, Marek (Zielona Góra: Uniwersytet Zielonogórski)
SNP sites are generally discovered by sequencing regions of the human genome in a limited number of individuals. This may leave SNP sites present in the region, but containing rare mutant nucleotides, undetected. Consequently, estimates of nucleotide diversity obtained from assays of detected SNP sites are biased.
Keywords: single nucleotide polymorphisms; ascertainment bias; nucleotide diversity; molecular evolution